Aldous Huxley’s Brave New World (1932) Through the Lens of Sheldon Wolin’s American “Inverted Totalitarianism” (2008) - Yahia,Djamila; Aribi, Brahim (University of Ammar Theledji -Laghouat, 2020)
A major preoccupation of postmodern scholars is the idea of waning democracy in the light of an increasing governmental repression. The present dissertation investigates the prophetic relevance of Aldous Huxley’s dystopian novel Brave New World (1932) to the political scene of the United States. It analogically traces aspects of Sheldon Wolin’s political theory “Inverted Totalitarianism” in the novel. Therefore, it hypothesizes that Brave New World’s government adopts a set of non-democratic repressive ideologies similar to those suggested in Wolin’s political theory. Hence, the current research undertakes a descriptive analytical approach to study the analogy between the novel’s control strategies and those depicted in Wolin’s Democracy Incorporated: Managed Democracy and the Specter of Inverted Totalitarianism (2008). It employs the Neo-Marxist and Foucauldian philosophical lenses to specifically explore aspects of power monopolization and discourse manipulation. The study ultimately concludes that the subjugation strategies employed by the New World government match to a large extent those used by the system of an Inverted Totalitarianism. Thus, the novel bares a strong prophetic ideological relevance to the American political scene